2013
DOI: 10.1111/jerd.12060
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Premolar Teeth Restored with Silorane‐Based or Dimethacrylate‐Based Composite Resins

Abstract: The findings of this study support the selection of silorane-based composite for the restoration of maxillary premolars with standardized Class II cavity preparations in order to strengthen the resistance to fracture to the same extent as do dimethacrylate composites using cavity liners or without them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Compressive strength values in sound maxillary premolars are approximately 1742±110 N, although the current study presented an 1114.3±157 N mean value of fatigue strength in the control group (C) (22).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Compressive strength values in sound maxillary premolars are approximately 1742±110 N, although the current study presented an 1114.3±157 N mean value of fatigue strength in the control group (C) (22).…”
Section: Discussionmentioning
confidence: 78%
“…Literature reports have shown that materials that exhibit high initial resistance do not always have high resistance to fatigue (5,6). Therefore, it seems appropriate that the strength of teeth restored with dental materials should be measured using a dynamic mechanical test rather than static tests (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Standardized MOD cavities were prepared with the gingival margin placed 1 mm coronal to the CEJ, using cylindrical diamond burs (ISO 806314, Hager & Meisinger, GmbH, Neuss, Germany). The cavity dimensions were: occlusal width = 2/3 of intercuspal width; pulpal depth = 2.5 mm; proximal box width = 1/2 of buccolingual dimensions; axial width = 2 mm; and axial depth = 1.5 mm . The facial and palatal walls of the cavities were parallel to the long axis of the teeth.…”
Section: Methodsmentioning
confidence: 99%
“…All the liners were applied in a thin layer (approximately 1 mm) on the pulpal and axial walls according to the respective manufacturers’ instructions. After finishing the completed restorations with Sof‐Lex discs (3M ESPE), they were stored in distilled water for 24 hours at 37°C and then thermocycled (Vafaie Inc, Tehran, Iran) for 1000 cycles at 5°C/55°C (dwell time: 15 seconds) . The specimens were subjected to a continuous compressive axial loading at a 1‐mm/min crosshead speed using a universal testing machine (Zwick Roell, Ulm, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Low‐shrinkage RBCs were developed to overcome the single most unfavorable property of RBCs, that is, polymerization shrinkage and the associated stress . These RBCs are used as posterior teeth restoratives and as such are expected to possess at least satisfactory optical and esthetic properties.…”
Section: Introductionmentioning
confidence: 99%